(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
: This thesis explores the mythological poetics in the dramaturgy of W. B. Yeats, focusing on how myth functions as a central element in his dramatic works. The study examines the role of Celtic mythology, symbolic imagery, and archetypal motifs in shaping Yeats’s theatrical vision. It highlights how mythological structures serve not only aesthetic purposes but also philosophical and cultural functions, reflecting historical memory, spiritual experience, and national identity. The analysis demonstrates that Yeats’s use of myth allows for a synthesis of poetic and theatrical elements, creating a multi-layered dramatic space that transcends the boundaries of time and realism. The findings underline the significance of myth as a tool for artistic innovation in Yeats’s dramaturgy and its impact on modernist theatre.